New economic policies and post-pandemic Spanish economic growth - Uxó, Jorge; Álvarez, Ignacio (Wirtschaft und Gesellschaft, 2026)
Since recovering the pre-pandemic GDP level in 2020, Spain has been recording growth rates well above the eurozone average. Furthermore, against a backdrop of demographic dynamism, Spanish per capita income is also growing, the employment rate is rising, and the unemployment rate has fallen below 10% for the first time in 17 years. Productivity growth has also accelerated, a novelty in Spain, where it has traditionally behaved countercyclically. We analyse the factors behind this behaviour of the Spanish economy, emphasizing the changes in economic policy implemented since 2020. These changes focus on fiscal and labour policies, the reinforcement of the welfare state, and the first steps of a new industrial policy, with an emphasis on the energy transition. Of course, some problems remain, such as the housing price crisis and the insufficient translation of productivity gains to wages.